Pengembangan dan Transformasi Pasar Kalangan (Pasar Kamis) Sebagai Pusat Perekonomian Syariah yang Tertib Administrasi, Profitable, Efisien, dan Berdaya Saing di Desa Tirta Kencana, Kabupaten Tebo - Amir, Amri; Ridhwan, Ridhwan; Enggraini Fitri, Luky; Lubis, Paulina; Syukri Amri, Adi Ihsan; Ananta Putri, Sashi (PT. Alahyan Publisher Sukabumi, 2025)
Development of Pasar Kalangan (Thursday Market) in Tirta Kencana Village, Tebo Regency, aims to enhance efficiency, governance, profitability, and competitiveness by implementing Sharia economic principles. The program focuses on improving administration, infrastructure, public services, and Sharia economic education. The expected outcomes include increased transactions, higher income for merchants, greater public awareness of Sharia economic principles, improved market facilities, and reduced user complaints. This transformation is expected to promote the welfare of the local community while strengthening Sharia values in market management.